RAILWAY INFRASTRUCTURE CAPACITY MANAGEMENT FOR AD-HOC TRAINS ON THE SŽDC NETWORK - Nachtigall, Petr; Škárek, Martin (České vysoké učení technické v Praze, 2016)
The paper describes basic principles of ad hoc routes assignment. Each carrier has its own interface called information system KADR with SŽDC for capacity requests management. The paper describes all steps which must be done before train departure.
Přidělování kapacity na síti SŽDC pro ad-hoc vlaky
Keywords: Information system; carrier; ad hoc train; railway infrastructure capacity; informační systém; dopravce; ad-hoc trasa; kapacita dráhy